The Influence of Environmentally Friendly HRM on Environmentally Friendly OCB: The Mediating Role of Organizational Identification, Job Satisfaction, and Environmentally Friendly Culture - Kristanto Prasetyo Aji; Asri Laksmi Riani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The goal of this research is to investigate how Green Human Resource Management (GHRM) impacts Green Organizational Citizenship Behavior (G-OCB), with the involvement of organizational identification, job satisfaction, and green culture. The methodology utilised for this study is a survey. The target group for this research comprises of postgraduate students from the Faculty of Economics and Business at Universitas Sebelas Maret, who are currently working in various sectors. A purposive sampling approach was employed, with a total of 140 participants. Analysis of the data was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study shows that GHRM has a notable impact on organizational identification, but organizational identification has no significant impact on G-OCB. In addition, GHRM has a significant influence on job satisfaction, while job satisfaction does not significantly affect G-OCB. Moreover, GHRM has a significant effect on green culture, and green culture also has a significant impact on G-OCB. The findings suggest that organizational identification does not act as a mediator between GHRM and G-OCB, and job satisfaction does not mediate the relationship either. However, green culture is found to be a mediator in the relationship between GHRM and G-OCB.